Radiation Therapy for Mucosal Melanoma of the Head and Neck. (February 2015) - Christopherson, Kaitlin; Malyapa, Robert S.; Werning, John W.; Morris, Christopher G.; Kirwan, Jessica; Mendenhall, William M.
Abstract : Objectives: The aim of this study was to evaluate the long-term effectiveness and complications of radiotherapy (RT) in the treatment of patients with mucosal melanomas of the head and neck. Materials and Methods: The medical records of 21 patients treated with definitive or postoperative (RT) between 1974 and 2011 at the University of Florida Department of Radiation Oncology in Gainesville, FL, and the University of Florida Proton Therapy Institute in Jacksonville, FL, were retrospectively reviewed under an Institutional Review Board-approved protocol. Primary sites included nasal cavity, oropharynx, and paranasal sinuses. Sixteen patients (76%) received surgery and postoperative RT and 5 patients (24%) received RT alone. Seventeen patients received photon RT alone, whereas 4 patients received combined photon-based and proton-based RT. Median follow-up for all patients was 1.05 years (range, 0.36 to 12.97 y); median follow-up for survivors was 2.2 years (range 0.9 to 13.0 y). Results: The 5-year outcomes were: local control, 79%; regional control, 85%; local-regional control, 65%; distant metastasis-free survival, 20%; cause-specific survival, 22%; and overall survival, 22%. Three patients (14%) experienced severe complications including bilateral blindness and skin necrosis. Conclusions: Definitive or postoperative RT for mucosal melanoma of the head and neck yields fairly good local-regional control of disease. The prognosis for patients treated with definitive RT is less promising than for those who receive surgery and postoperative RT.